Investigating challenges among the families of children with Autism Spectrum Disorder (ASD) in Internally Displaced People (IDP) camps in South East and North Central regions of Nigeria. - Dorothy Nkem Ezenwanne (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The challenges faced by families of children with Autism Spectrum Disorder (ASD) in Internally Displaced Persons (IDP) camps are exacerbated by the unique context of displacement. In Nigeria, the ongoing humanitarian crisis due to conflicts, natural disasters, and other socio-political factors has led to a significant increase in the number of IDPs, with many seeking refuge in camps across the South East and North Central regions. The study adopted a descriptive survey design to explore challenges faced by families of children with Autism Spectrum Disorder (ASD) in IDP camps in South East and North Central Nigeria. A sample of 80 participants was drawn using a stratified sampling technique. Data were collected through a validated and reliable questionnaire, capturing demographic details and relevant challenges. Descriptive statistics, including mean, standard deviation, variance, and harmonic mean, were used to summarize findings, while hypotheses were tested using Analysis of Variance (ANOVA). Among 80 participants, most caregivers were younger than 35 years (67.5%) and unemployed (46.3%). Financial, emotional, and social challenges varied by caregivers’ age and camp duration. Families staying over 12 months reported higher financial challenges (mean = 18.67, SD = 3.98). Emotional challenges were highest for parents aged 46+ years staying 3 months (mean = 21.67). Social challenges followed similar patterns. ANOVA results showed no significant differences in challenges across groups, emphasizing universal difficulties faced by families. The findings emphasize the urgent need for targeted interventions, including increased awareness campaigns, capacity-building programs for caregivers, and improved access to essential services such as therapy, education, and mental health support within IDP camps.